2022
DOI: 10.3390/diagnostics12020391
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Detection Using Support Vector Machine Method Based on Spectralis OCT

Abstract: Spectralis optical coherence tomography (OCT) provided more detailed parameters in the peripapillary and macular areas among the OCT machines, but it is not easy to understand the enormous information (114 features) generated from Spectralis OCT in glaucoma assessment. Machine learning methodology has been well-applied in glaucoma detection in recent years and has the ability to process a large amount of information at once. Here we aimed to analyze the diagnostic capability of Spectralis OCT parameters on gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Therefore, the diagnostic value of these new parameters must be explored, particularly in the detection of early glaucoma. As we reported previously, through machine learning, Spectralis OCT exhibits a good differentiation ability for various stages of glaucoma among the Chinese population in Taiwan 31,32. Using Spectralis OCT in the present study, we evaluated the diagnostic capacity of its various individual parameters for different subtypes of early glaucoma in the Chinese population in Taiwan.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, the diagnostic value of these new parameters must be explored, particularly in the detection of early glaucoma. As we reported previously, through machine learning, Spectralis OCT exhibits a good differentiation ability for various stages of glaucoma among the Chinese population in Taiwan 31,32. Using Spectralis OCT in the present study, we evaluated the diagnostic capacity of its various individual parameters for different subtypes of early glaucoma in the Chinese population in Taiwan.…”
Section: Discussionmentioning
confidence: 66%
“…As we reported previously, through machine learning, Spectralis OCT exhibits a good differentiation ability for various stages of glaucoma among the Chinese population in Taiwan. 31,32 Using Spectralis OCT in the present study, we evaluated the diagnostic capacity of its various individual parameters for different subtypes of early glaucoma in the Chinese population in Taiwan. Furthermore, we attempted to enhance the diagnostic capacity of the individual parameters by using multiple logistic regression models developed using all parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed study characteristics are presented in Table 1. A total of 20 studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] were included in the article which comprises 51 models. The studies were published in years from 2014 to 2023 and involved 13 diverse countries/regions [Australia, Brazil, China, India, Japan, Korea, Pakistan, Singapore, Romania, Spain, Taiwan (China), United States, and Nepal], two of which were multicenter surveys.…”
Section: Study Characteristicmentioning
confidence: 99%
“…Chao-Wei et al [106] aimed to evaluate performance of Spectral is OCT parameters on glaucoma detection using the SVM classification approach. Our results showed that the SVM technique combined with all OCT features had good performance in detecting the area under the curve of glaucomatous eyes as well as discriminating early, moderate, or severe glaucoma and normal eyes.…”
Section: A) Glaucoma Detection Using Machine Learning Techniquesmentioning
confidence: 99%